Ear Foreign Body Extraction - Isyraq Althaf Junidar Mantika (Rifa'Institute, 2022)
Ear foreign body removal is a common procedure performed in the emergency department that can happen to anyone, both children and adults. The method used in writing this literature review is a literature review. Article writing consists of several sources originating from journals and related agency guidelines. Source searches were conducted on online portals for journal publications such as Medscape, Research gate and the National Center for Biotechnology Information/NCBI (ncbi.nlm.nih.gov), with the keyword used being “ear foreign body”. Various kinds of foreign objects have been reported to have entered the ear canal including insects, beads, paper and so on. Foreign body removal techniques consist of manual instrumental, irrigation, and suctioning. Removal of foreign bodies should not be performed if the patient is suspected of having a perforation of the tympanic membrane. Removal of a foreign body from the ear canal depends on the type of foreign body present in the ear canal.